Economic evaluation of bariatric surgery to combat morbid obesity: A study from the West of Scotland. Issue 3 (3rd July 2013) - Karim, Muhammad Ali; Clifton, Edward; Ahmed, Jamil; Mackay, Gordon William; Ali, Abdulmajid
Abstract Introduction The increasing prevalence of obesity has now become a global concern. Forecasts of its health and financial ramifications have prompted the need for effective interventions. Bariatric surgery is an effective measure to control obesity and its related comorbidities, but its high upfront costs have raised questions about its cost‐effectiveness. In this study we evaluated the health care‐related direct cost savings after bariatric surgery. Methods Data were prospectively obtained from patients who underwent bariatric surgery between May 2008 and April 2011, and a review was performed. These patients' annual cost of regular medications, hospital admissions and outpatient clinic visits were compared with the postoperative costs of these services. Data were collected from January 2005 to April 2012. Results The analysis included 88 patients, 17 of whom were men and 71 were women. The procedures included 36 laparoscopic adjustable gastric banding, 33 sleeve gastrectomies and 19 Roux‐en‐Y gastric bypasses. All procedures were laparoscopic. Data were collected from patients during a median preoperative period of 60 months (range, 42–75 months) and a median postoperative period of 24 months (range, 12–45 moths). Annual savings were £11 452 on medications, £16 420 on hospital admissions and £2532 on outpatient clinic visits. Total annual savings were £30 404. Conclusion Given the rising prevalence of morbid obesity, bariatric surgery is a cost‐effective treatment for morbid obesity and should be made available to morbidly obese patients.